ChemInform Abstract: Free‐Amine Directed Arylation of Biaryl‐2‐amines with Aryl Iodides by Palladium Catalysis. Issue 5 (4th February 2014) - Liang, Zunjun; Feng, Ruokun; Yin, Hong; Zhang, Yuhong
Abstract The title method allows the synthesis of ortho‐monoarylated or diarylated biaryl‐2‐amines with exclusive regioselectivity.